2017
DOI: 10.1080/13691457.2017.1318833
|View full text |Cite
|
Sign up to set email alerts
|

Making the transition from practitioner to supervisor: reflections on the contribution made by a post-qualifying supervisory course

Abstract: Acknowledgments:The ideas presented in the article are developed from teaching on a post-qualifying course for managers and supervisors in Scotland's social services. Thanks are due to course participants for their engagement, commitment and contribution. 2 AbstractWithin Scotland, as elsewhere, there has been a resurgence of interest in the critical role of supervision within social work practice. Notwithstanding this interest, those making the transition from practitioner to supervisor still commonly report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…By their nature, social service organisations are complex systems with unique aspects related to supervision transition. For instance, Patterson and Whincup (2018) assert that as social service supervisors transition into their new roles, they are required to navigate from familiar to unfamiliar settings. Parker (2014:24) asserts that "the supervisor-supervisee relationship can be of a professional or anti-discriminatory nature" and adds that an anti-discriminatory approach as significant in South Africa, "as it is likely that the supervisor and supervisee are from different cultural or religious backgrounds".…”
Section: Supervision Learning In Social Service Organisationsmentioning
confidence: 99%
See 1 more Smart Citation
“…By their nature, social service organisations are complex systems with unique aspects related to supervision transition. For instance, Patterson and Whincup (2018) assert that as social service supervisors transition into their new roles, they are required to navigate from familiar to unfamiliar settings. Parker (2014:24) asserts that "the supervisor-supervisee relationship can be of a professional or anti-discriminatory nature" and adds that an anti-discriminatory approach as significant in South Africa, "as it is likely that the supervisor and supervisee are from different cultural or religious backgrounds".…”
Section: Supervision Learning In Social Service Organisationsmentioning
confidence: 99%
“…Goliath (2018) found that transitioning from the level of a social work practitioner to the supervision level raises significant challenges. Patterson and Whincup (2018) also assert that enhancing an understanding of the supervisory task provides the incumbents with the capacity to sustain active and reflective supervision in the face of conflicting demands.…”
Section: Subtheme 21: Professional Autonomy and Organisational Demand...mentioning
confidence: 99%